Role of Vascular Surgery in Diabetic Foot Management - Benyakorn, Thoetphum (Journal of the Association of General Surgeons of Thailand under the Royal of Patronage of HM the King, 2020)
Now, Diabetes is becoming the world problem due to aging population. The target organ damage of DM are eye, kidney and foot. Diabetes foot is a complex disease which will be affected in the lifetime of DM patient. This disease is the result of disorder of three systems; vascular, neurological and bone. The principle treatments of diabetic foot are control of blood glucose, effective local wound care, infection control, pressure relieving strategies and restoring of pulsatile blood flow. Many literatures demonstrated that DM is strongly associated with Peripheral arterial disease (PAD). Role of vascular surgeon is not only revascularization but also include of screening in high risk group, wound dressing, debridement, amputation and prevention of recurrence. For the best treatment result, the multidisciplinary team is the best option for caring of DM foot patient.